Diseño y puesta en marcha de un regulador de velocidad para la turbina de la Planta Hidroeléctrica Aguas Zarcas Sitio 1 - Elizondo-Rodríguez, Francisco (Instituto Tecnológico de Costa Rica, 2019)
The project was developed in Hidroeléctrica Aguas Zarcas Sitio 1 Company, which is a plant that is more than twenty-three years old, however, it was acquired by Coopelesca just five years ago and it is the smallest that the cooperative has, generating 1 MW of power. The plant has a Francis-type hydraulic turbine, which needs an electronic speed regulator responsible for controlling the flow of water that enters the turbine to work properly. In this plant the speed regulator was damaged three years ago, due to this the control of the machine was done manually, that is, the operators had to intervene in the control of the turbine flow, which is the critical point for the coupling of the group to the general network, level control, power and setting the distributor opening percentage (internal mechanism of the turbine that controls the flow of water). According to Coopelesca, with the speed regulator, the efficiency and safety of the plant is increased, since the connection time of the plant is reduced, the use of water is improved, there is a greater use of personnel in the plant and it eliminates possible human errors in the functions that the regulator now does automatically. This report shows the design process of the speed regulator through a PID controller, its implementation in the plant's controller (PLC) and the verification of its operation through simulations and commissioning tests.
Proyecto de Graduación (Licenciatura en Ingeniería en Electrónica). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica,2019.
Keywords: Turbinas Hidroeléctricas; Velocidad; Máquinas; Plantas Hidroeléctricas; Reguladores; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electric power engineering